Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep29076
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Lipid Virulence Factors Reduces the Efficacy of the BCG Vaccine

Abstract: Bacille Calmette-Guérin (BCG), an attenuated strain of Mycobacterium bovis, is the only vaccine available for tuberculosis (TB) control. BCG comprises a number of substrains that exhibit genetic and biochemical differences. Whether and how these differences affect BCG efficacy remain unknown. Compared to other BCG strains, BCG-Japan, -Moreau, and -Glaxo are defective in the production of phthiocerol dimycocerosates (PDIMs) and phenolic glycolipids (PGLs), two lipid virulence factors. To determine if the loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…A further advantage of mouse models is their ease for genetic manipulation. Recently, several immunodeficient and gene knockout mouse models, including severe combined immune deficiency (SCID) mice [63], C3HeB/FeJ mice (model of liquefactive necrosis and necrotic granulomas) [64,65], CBA/J IL-10(−/−) mice (mature, fibrotic M. tuberculosis-containing pulmonary granulomas) [66], C57BL/6 RAG(−/−) mice (small and diffuse lesions, with the majority of the lung retaining the typical lacy alveolar appearance of normal lung tissue) [67], C57BL/6 IL-17(−/−) mice (less densely packed granulomas with mononuclear cells) [68], and iNOS knockout mice (granulomas similar to those that form in humans) [69], have been used to study particular immune responses to mycobacterial infections. However, accumulating evidence shows that M. tuberculosis infection could induce neither caseous granuloma nor central necrosis in the most widely used mouse models (except for C3HeB/FeJ mice) [70,71], which was entirely different to the pattern observed in humans and guinea pigs [30].…”
Section: Rabbitsmentioning
confidence: 99%
“…A further advantage of mouse models is their ease for genetic manipulation. Recently, several immunodeficient and gene knockout mouse models, including severe combined immune deficiency (SCID) mice [63], C3HeB/FeJ mice (model of liquefactive necrosis and necrotic granulomas) [64,65], CBA/J IL-10(−/−) mice (mature, fibrotic M. tuberculosis-containing pulmonary granulomas) [66], C57BL/6 RAG(−/−) mice (small and diffuse lesions, with the majority of the lung retaining the typical lacy alveolar appearance of normal lung tissue) [67], C57BL/6 IL-17(−/−) mice (less densely packed granulomas with mononuclear cells) [68], and iNOS knockout mice (granulomas similar to those that form in humans) [69], have been used to study particular immune responses to mycobacterial infections. However, accumulating evidence shows that M. tuberculosis infection could induce neither caseous granuloma nor central necrosis in the most widely used mouse models (except for C3HeB/FeJ mice) [70,71], which was entirely different to the pattern observed in humans and guinea pigs [30].…”
Section: Rabbitsmentioning
confidence: 99%
“…Interestingly, studies also highlighted the role of PGL in BCG efficacy, where a mutant BCG (deleting fadD28) lacking both PDIMs and PGLs not only made BCG more attenuated in mice but also reduced its efficacy as a vaccine against M. tuberculosis infection (148). The terminal mannose residue of PIM 4 can be further substituted at position C-2 by a α-D-mannosyl leading to PIM 5 , which can also be further substituted at the same position leading to PIM 6 , the higher PIM encountered in mycobacteria to date (10).…”
Section: The Pgl Familymentioning
confidence: 99%
“…These lipids induce rapid and robust innate immune responses that lead to tissue inflammation and damage 16 or are used by mycobacteria to subvert host immunity 13,1720 . However, recombinant BCG strains deficient in specific lipids or a combination of these lipids are weak inducers of immune responses that protect mice against M.tb 21 . Thus, it is suggested that complete absence of the cell wall lipids is detrimental to the generation of immunity, but their presence is responsible for lung pathology.…”
Section: Introductionmentioning
confidence: 99%